Controlled dephasing of an electron interferometer with a path detector at equilibrium - Weisz, E; Choi, H K; Heiblum, M; Gefen, Yuval; Umansky, V; Mahalu, D (Physical review letters, 2012)
Controlled dephasing of electrons, via "which path" detection, involves, in general, coupling a coherent system to a current driven noise source. However, here we present a case in which a nearly isolated electron puddle within a quantum dot, at thermal equilibrium and in millikelvin range temperature, fully dephases the interference in a nearby electronic interferometer. Moreover, the complete dephasing is accompanied by an abrupt π phase slip, which is robust and nearly independent of system parameters. Attributing the robustness of the phenomenon to the Friedel sum rule--which relates a system's occupation to its scattering phases--proves the universality of this powerful rule. The experiment allows us to peek into a nearly isolated quantum dot, which cannot be accessed via conductance measurements.